Inhibition of Akt Attenuates RPO-Induced Cardioprotection - Emma Katengua-Thamahane; Anna-Mart Engelbrecht; Adriaan J. Esterhuyse; Jacques Van Rooyen (Cardiology Research and Practice)
Previous studies have shown that red palm oil (RPO) supplementation protected rat hearts against ischaemia-reperfusion injury. Evidence from these studies suggested that Akt may be partly responsible for the observed protection. The aim of the current study was therefore to prove or refute the involvement of Akt in the RPO-induced cardioprotection by administration of a specific Akt inhibitor (A6730). Male Wistar rats were randomly divided into 2 groups: a control group receiving standard rat chow and an experimental group receiving standard rat chow plus 2 mL RPO for six weeks. Hearts were excised and mounted on the Langendorff perfusion system. Functional recovery was documented. A different set of hearts were freeze-clamped to assess total and phosphorylation status of Akt. Another set of hearts were subjected to the same perfusion conditions with addition of A6730. Hearts from this protocol were freeze-clamped and assessed for total and phospho-Akt. RPO improved functional recovery which was associated with increased phosphorylation of Akt on Ser473 and Thr308 residues. Blockade of Akt phosphorylation caused poor functional recovery. For the first time, these results prove that Akt plays an important role in the RPO-induced cardioprotection.